2023
DOI: 10.3389/fpsyt.2022.1070142
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of structural and functional alterations of brain in patients with attention-deficit/hyperactivity disorder

Abstract: BackgroundA large and growing body of neuroimaging research has concentrated on patients with attention-deficit/hyperactivity disorder (ADHD), but with inconsistent conclusions. This article was intended to investigate the common and certain neural alterations in the structure and function of the brain in patients with ADHD and further explore the differences in brain alterations between adults and children with ADHD.MethodsWe conducted an extensive literature search of whole-brain voxel-based morphometry (VBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 123 publications
0
7
1
Order By: Relevance
“…In contrast to prior meta-analyses [19,20], low-risk ADHD subjects did not exhibit any signi cant cortical thickness or subcortical de cits compared with HC. The only signi cant morphological abnormality exhibited by the LR group was greater right pars opercularis surface area.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to prior meta-analyses [19,20], low-risk ADHD subjects did not exhibit any signi cant cortical thickness or subcortical de cits compared with HC. The only signi cant morphological abnormality exhibited by the LR group was greater right pars opercularis surface area.…”
Section: Discussioncontrasting
confidence: 99%
“…Speci cally, ADHD youth with a BD family history exhibited smaller bilateral thalamic, hippocampal, and left caudate volumes, and lower parietal, temporal and anterior cingulate cortex (ACC) surface area, compared with HC. Some of these regional de cits have previously been reported in youth with ADHD, including smaller caudate and hippocampus volumes [19,20], as well as rst-episode BD patients, including smaller temporal, parietal, orbitofrontal, and superior frontal cortical volumes [21,22]. Moreover, unaffected subjects with a BD family history exhibited reduced orbitofrontal and superior frontal cortical volumes [32,56].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a study with a relatively large sample size of adult ADHD patients, gray matter abnormalities in localized prefrontal and cerebellar regions were associated with working memory and inattention symptoms (Duan et al, 2018), and these results were found to be consistent with the theory of cognition dysfunction mediated by inferior fronto-striato-cerebellar network in ADHD (Rubia, 2011). In a recent meta-analysis, it was suggested that abnormal alterations in the structure and function of the left superior frontal gyrus and corpus callosum may be key brain regions involved in the pathogenesis of ADHD (Yu et al, 2023). Further studies investigating the neural correlates of the ToM in ADHD are needed.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many studies have found that the overall brain volume of ADHD patients decreases by 3−5%, and gray matter is affected first (Greven et al, 2015), and the cortical thickness of frontal lobe, temporal lobe and insular lobe were also decreased (Hoogman et al, 2019;Maier et al, 2023). In terms of gray matter volume, studies have found that ADHD patients have reduced cortical gray matter volume in the right basal ganglia and insula (Norman et al, 2016), and the gray matter volume in the amygdala and hippocampus were also decreased (Yu et al, 2022). Furthermore, in a study on gender differences, it was found that the gray matter volume of the left lingual gyrus is reduced in male children with ADHD (Gonchigsuren et al, 2022).…”
Section: Figurementioning
confidence: 98%